Joseph Ingraham journal - Ingraham, Joseph, 1762-1800.
Four volumes containing Ingraham's account of the voyage of the brigantine Hope from Boston to the Falkland Islands; Cape Horn, Chile; Marquesas Islands, French Polynesia; the Northwest Coast of North America; the Sandwich Islands (Hawaii); and China. Documents commercial trade, especially the fur trade, with China. Includes descriptions and drawings of fauna, flora, and inhabitants; charts; and maps of various locations including several Marquesas Islands discovered and named by Ingraham during the voyage.
Microfilm edition available
Microfilm edition (color reel) of several illustrations available
Microfilm produced from originals in the Manuscript Division.
Navigator, trader, and explorer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hope (Brigantine); Fur trade -- Northwest Coast of North America; Ship's papers -- 18th century; Voyages and travels; Voyages to the Pacific coast; China -- Commerce -- United States; Falkland Islands -- Description and travel; Hawaii -- Description and travel; Horn, Cape (Chile) -- Description and travel; Marquesas Islands (French Polynesia) -- Discovery and exploration; Northwest Coast of North America -- Description and travel; Oceania -- Discovery and exploration; Pacific Ocean -- Discovery and exploration; United States -- Commerce -- China; Explorers; Navigators; Traders